The implementation of 3D for learning shrouding muslim dead body (Kaffan Method) / Nor Aizura Jama Rusly - Jama Rusly, Nor Aizura Jama Rusly (2004)
Nowadays, 3D has become popular especially on games environment and genre. However, in Malaysia, the 3D development is still at infancy stage. This project, tries to apply 3D in learning environment. It is also provide some insights on how some 3D animations should be created. Apart from that, this project identifies the nature and the elements needed to develop learning application. The implementation of this project is based on the Courseware Life Cycle Model, which is a combination of waterfall and prototype software life cycle model. Software develop are contains a short notes, 3D movie, 3D simulation and simple exercises